An empirical perspective on auctions - Ken Hendricks; Robert H. Porter (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
We describe the economics literature on auction markets, with an emphasis on the connection between theory, empirical practice, and public policy, and a discussion of outstanding issues. We describe some basic concepts, to highlight some strengths and weaknesses of the literature, and so indicate where further research may be warranted. We discuss identification and estimation issues, with an emphasis on the connection between theory and empirical practice. We also discuss both structural and reduced form empirical approaches.
Keywords: 330; Auctions; bidding; identification; estimation; collusion; bid rigging